Adsorption of methylene blue onto xanthogenated-modified chitosan microbeads / Zurhana Mat Hussin … [et al.] - Mat Hussin, Zurhana; Ismail, Mardhiah; Megat Hanafiah, Megat Ahmad Kamal; Ghazali, Siti Nadzifah; Mohd Jan, Sarah Laila; Mohd Khaazai, Siti Norhafiza; Zakaria, Siti Raihan (2013)
Methylene Blue (MB) is thiazine dyes that is widely used to color product in many industry such as textile, printing, leather, cosmetic and paper. Xanthogenated-Modified Chitosan Microbeads (XMCM) is used to observe the new alternative adsorbent in removing MB from water body through adsorption process. The interactions between MB and functional group in XMCM were confirmed by Fourier Transform Infrared (FT-IR) Spectra. Several parameters that influence adsorption ability such as the effect of adsorbent dosage of XMCM and the effect of initial pH of MB aqueous solution were studied. This study was done at an optimum condition which is at pH 4 of initial pH of MB solution, 0.01 g of initial XMCM dosage, 6 hours stirring time and temperature of (30 ± 2°C). The adsorption data fitted well Langmuir model more than Freundlich model. Based on Langmuir model, the maximum monolayer adsorption capacity of MB was 21. 62 mg g-1 which indicated that XMCM can be a new alternative adsorbent for removing MB.